Analisis Faktor-Faktor yang Mempengaruhi Kinerja Pelabuhan Stagen dan Tarjun - Ahmad Nurul Huda; Iphan Fitrian Radam (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Indonesia, as an archipelagic country, relies heavily on maritime transportation to support regional connectivity. The Stagen and Tarjun Ferry Ports play an important role in community mobility and logistics distribution in South Kalimantan. Improved access through Jalan Gubernur H. Sahbirin Noor has increased ferry users, but service quality and infrastructure have not improved accordingly. This study aims to analyze the factors affecting port performance using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through questionnaires distributed to port users. Of the 47 indicators evaluated, 11 reflective and 16 formative indicators met the SEM-PLS model criteria. The findings identified five factors influencing port performance: port facilities, ferry facilities, operational systems, operators, and supporting facilities. Operational systems and supporting facilities were the most influential factors, particularly regarding waiting time, waiting room comfort, parking capacity, and service schedule accuracy. Therefore, improving facilities and optimizing operational systems are the primary strategies for enhancing ferry port service quality.